A study of the effect of bulges on bar formation in disc galaxies. Issue 2 (26th December 2017) - Kataria, Sandeep Kumar; Das, Mousumi
Abstract: We use N -body simulations of bar formation in isolated galaxies to study the effect of bulge mass and bulge concentration on bar formation. Bars are global disc instabilities that evolve by transferring angular momentum from the inner to outer discs and to the dark matter halo. It is well known that a massive spherical component such as halo in a disc galaxy can make it bar stable. In this study, we explore the effect of another spherical component, the bulge, on bar formation in disc galaxies. In our models, we vary both the bulge mass and concentration. We have used two sets of models: one that has a dense bulge and high surface density disc, and the other model has a less concentrated bulge and a lighter disc. In both models, we vary the bulge to disc mass fraction from 0 to 0.7. Simulations of both the models show that there is an upper cut-off in bulge-to-disc mass ratio M b / M d above which bars cannot form; the cut-off is smaller for denser bulges ( M b / M d = 0.2) compared to less denser ones ( M b / M d = 0.5). We define a new criterion for bar formation in terms of the ratio of bulge to total radial force ( F b / F tot ) at the disc scale lengths above which bars cannot form. We find that if F b / F tot > 0.35, a disc is stable and a bar cannot form. Our results indicate that early-type disc galaxies can still form strong bars in spite of having massive bulges.